qanda-logo
search-icon
Símbolos
apple-logo
google-play-logo
Problema
solution-image
$11$ Reescribe la ecuación completando el cuadrado. $2x^{2}+3x-12=0$ $=$ $x^{2}+\dfrac {3x} {2}+\left(\dfrac {3} {4}\right)^{2}=$ $\dfrac {12} {2}+\dfrac {9} {16}$ $x^{2}+\dfrac {3} {2}x+\left(\dfrac {3} {4}\right)^{2}=\dfrac {105} {16}$ $=\left(2\left(x+\dfrac {3} {4}\right)^{2}-\dfrac {105} {8}$ $=0$ $x^{2}+18x+92=0$ $=$ $x^{2}-10x+32=0$ $=$ $3x^{2}-4x-5=0$ $=$ $=$ $\dfrac {5} {3}+\dfrac {16} {36}$ $=\dfrac {19} {9}$ $=\left($ $3\left(x+\dfrac {2} {3}\right)^{2}-\dfrac {19} {3}=0$
Secundaria
Otra
Búsquedas: 130
Solución
answer-user-profile-image
Profesor de Qanda - milagros
answer-reply-image